The development of the fuzzy-based infant incubator - Adam, Ismail; Rozi, Husnatul Fatihah; Khan, Sheroz; Zaharuddin, Zarimin; Abdul Kadir, Kushairy; Nordin, Anis Nurashikin (AIP Publishing, 2019)
In the Bio-medical field, preterm infant care is one of the most important and popular areas of study. The newborns are at a higher risk of mortality and are called high-risk infants because of the gestational age or their birth weight put them at higher-than-average risk of disease and death. For that purpose, the preterm baby requires surrounding exactly similar as in the womb to cope with the external environment. This paper addresses the development of the fuzzy-based infant incubator which controlled the temperature and humidity. The objective of this paper is to design and develop the fuzzy-based controlled incubator to regulate temperature and humidity at a maximum error of 0.5℃ and 5% respectively. The novelty of this paper is in the temperature and humidity range regulated